Nerve Growth Factor Levels in Term Human Infants: Relationship to Prenatal Growth and Early Postnatal Feeding - David Sánchez-Infantes; Rubén Cereijo; Giorgia Sebastiani; Miriam Pérez-Cruz; Francesc Villarroya; Lourdes Ibáñez (International Journal of Endocrinology)
Background. Nerve growth factor (NGF) plays a key role in neuroprotection and developmental maturity. We assessed longitudinally the circulating concentrations of NGF in term healthy human newborns and infants as well as their association with prenatal growth and early postnatal feeding patterns. Methods. Circulating NGF and anthropometric measures (weight, length, body mass index, and ponderal index) were assessed longitudinally—at birth and at age 4 months—in 86 term infants born appropriate (AGA), small (SGA), or large for gestational age (LGA). Results. Cord blood NGF levels in SGA newborns were higher than those in AGA newborns (1.41 ± 0.2 pg/mL vs. 0.66 ± 0.1 pg/mL; p=0.02) and not different from those in LGA neonates (0.79 ± 0.2 pg/mL). At age 4 months, SGA-breastfed infants showed the highest NGF concentrations (p=0.02 and p=0.01 vs. AGA and SGA-formula-fed infants, respectively), while LGA infants depicted a marginal increase. NGF levels in cord blood correlated negatively with the ponderal index at birth (r=−0.36; p=0.0008). Conclusions. Circulating NGF is related to both prenatal growth and early postnatal nutrition. The maintenance of increased NGF concentrations in SGA-breastfed infants at age 4 months might be a potential mechanism to counterbalance potential risks for developing cognitive and psychomotor disadvantages.